Las características del currículo colonizado desde una perspectiva teórico-social - Villavicencio Santillán, Washington Rolando (2016)
This article is intended to describe the results of the analysis of the theoretical framework in the thesis named: The colonized curriculum and its impact on professional education. From this perspective, cultural leftovers from colonial era are analyzed and how they are still placed in some components of college education. The expressions of this phenomenon can be found in human behavior in the context of social structures which orbits around a work logic and prevent educational dynamics from giving the professional a holistic and integral education. Likewise, it becomes complex that the social being can develop through processes harmonizing competences of an intellectual, social, bio-psychological and work kind oriented to the compromise of education not from a work perspective but from a social perspective that can be determined by the application of ancestral knowledge and adopt commitment of incorporating to the curriculum contextualized elements of own descending kind so that they go beyond pedagogical practices as receipts that inoculates into the educational system and its processes. This constitutes a problem that presents itself as a new receipt from a colonized structure that is incompatible with the pursuit of educational identity of countries.